Review and key to all known species of the genus Epacromius Uvarov, 1942 (Orthoptera: Acrididae) - Lu, Ying; Wang, Li-Ming; Ren, Bing-Zhong (Zootaxa, 2016)
This paper provides a review and key to all species of the genus Epacromius Uvarov, 1942. The first description of the male of the species Epacromius fallax Wang, 2007 is given.